Sharing a Hybrid Electronic Health Record + Fast Healthcare Interoperability Resources Clinical Decision Support across Health Systems: Automating Smoking Cessation for Pediatric Caregivers - Saleh, Sameh N.; Kim, Eric; Thayer, Jeritt G.; Nabi-Burza, Emara; Karavite, Dean J.; Winickoff, Jonathan P.; Fiks, Alexander G.; Jenssen, Brian P.; Riley, Nicholas; Grundmeier, Robert W. (Applied Clinical Informatics, 2025)
Experiences sharing complex workflow-integrated clinical decision support (CDS) across health systems are sparse and not well reported. This case study presents the sharing of a hybrid electronic health record (EHR)-native and SMART-compatible CDS tool for automating provision of smoking cessation treatment for caregivers during pediatric visits.We conducted a comprehensive needs assessment using sociotechnical frameworks to identify workflow gaps and technical requirements. A multidisciplinary team of clinical informaticians, software developers, and EHR analysts guided the technology transfer. Iterative testing and feedback informed modifications. The evaluation tracked questionnaire uptake, tobacco use identification rates, and treatment acceptance metrics.The needs assessment revealed critical artifacts such as data architecture, source code repositories, and regulatory requirements, which informed adaptations for the recipient health system. In the preimplementation phase, JXPORT was identified for transferring EHR-native components and the EHR's Active Guidelines Framework was needed to extend the Fast Healthcare Interoperability Resources standard with ordering, posting flowsheet values, and launching activities in the embedded web application. The implementation process resulted in key modifications including same-day nicotine replacement therapy delivery through internal pharmacy services and optimized questionnaire design to improve usability. At the source system, 5.8% (n = 3,391) of caregivers reported active tobacco use with 46.9% (n = 1,590) accepting cessation resources. At the recipient system, 24.3% (n = 167) of caregivers listed tobacco use and 28.1% (n = 47) accepted treatment.The cross-system sharing of eCEASE serves as a nascent model for disseminating complex CDS tools and highlighted opportunities for improvement. Future work should focus on creating validated dissemination frameworks and improving use of standards for EHR integration.
Keywords: EHR-native; FHIR; clinical decision support; smoking cessation; pediatric visits; dissemination; interoperability; technology transfer